Depression, anxiety, and behavioural changes during the Covid-19 pandemic among medical and nursing students - Mohd Arifin, Siti Roshaidai; Saiful Azmi, Siti Mardhiah; Abang Abdullah, Khadijah Hasanah; Abas, Nurul Ain Hidayah; Husain, Rohayah; Aidid, Edre; Karimah Hanim, Abdul aziz; Musa, Ramli; Syed Mohideen, Fathima Begum; Perveen, Asma; Che Mat, Khairi; Idris, Izazol (Tech Science Press, 2022)
During the COVID-19 pandemic, medical and nursing students are faced with various challenges such as the need to attend online classes and juggling clinical postings under the new norm. This study aimed to assess the association between depression, anxiety, and behavioural changes among medical and nursing students during the COVID-19 pandemic. An online self-administered questionnaire was distributed between March 2021 and July 2021 to 292 undergraduates medical and nursing students in a higher education institute on the East Coast of Malaysia. The questionnaires consisted of four parts: sociodemographic data, the Generalised Anxiety Disorder-7, the Patient Health Questionnaire-9, and questions related to behaviours during the COVID-19 pandemic. This study found that 23.6% and 33.6% of the students experienced anxiety and depression respectively, possibly caused by the COVID-19 pandemic. Anxiety was associated with a high level of behavioural changes during the pandemic with a total of 87% of the students showing behavioural changes. Therapeutic interventions such as online counselling and consultation should be implemented by the university to reduce the prevalence of depression and anxiety resulting from the COVID-19 pandemic among medical and nursing students.